Pengaruh Kompensasi terhadap Kepuasan Kerja Karyawan pada PT. Sinar Agus Tehnik Jambi - Cici Gustiandasari (Science of Management and Students Research Journal (SMS), 2020)
This research above to know and analize whether the discipline and work productivity at PT. Sumbertama Nusa Pertiwi is good, to know and analize of discipline to work productivity of employees at PT. Sumbertama Nusa Pertiwi. This study includes a descriptive study to test the hypotesis, sampel this study were employees PT. Sumbertama Nusa Pertiwi of 34 People, with a population census method as respondents in answering the questionnaire. The technique of colleting data using questionaires. Data analisys technique used was SPSS with simple regresi analisys and t test. The influene of compensation on employee job satisfaction at PT. Sinar Agus Tehnik Jambi is Y = 10,200 + 0,562 X + e, There is a positive relationship between compensation to employee job satisfaction at PT. Sinar Agus Tehnik Jambi. The constant is 10,200, meaning that if the compensation variable is fixed, then the job satisfaction of employees at PT. Sinar Agus Tehnik Jambi amounting to 10,200. The compensation variable coefficient is 0.562, meaning that if compensation rises 1% then employee job satisfaction increases by 0.562% .Based on the t test it’s known that compensation has  a signnificant positive  effect on  employee job satisfaction.